MAIMONIDES ON KINGSHIP The Ethics of Imperial Humility - Diamond, James A. (Journal of religious ethics, 2006)
In his adoption of the Maimonidean guidelines for extreme humility, the king acts as the supreme existential model for imitatio dei. Imperial governance, when filtered through the prism of Maimonidean humility, results in a regime that most closely resembles a divine one. Using those who occupy the very bottom of the social and political hierarchy (slaves and orphans) as models, the king projects his own sense of “lowliness” to the people. The king thereby promotes their sense of autonomy, and inhibits any anthropocentrism that would be fostered if he were to be viewed as an autocrat. His administration of the royal office is limited by the ethical and philosophical dictates of humility, thereby offering a window into the distinction between its common (anivut) and extreme (shefal ruah) manifestations. Maimonides does in fact define the parameters of this extraordinary humility, but he chooses to do so within the context of a distinct and concrete personality—that of the king.